2017
DOI: 10.1590/0034-7167-2016-0523
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Theory of Breastfeeding: creation and application of a middle-range theory

Abstract: Objective: To describe a breastfeeding theory based on King's Conceptual System. Method: Theoretical study that used analysis of concept, assertion synthesis, and derivation of theory for the creation of a new theory. Results: King's system components were associated with elements of the breastfeeding process and a middle-range theory was created, which describes, explains, predicts, and prescribes breastfeeding by analyzing factors that precede and affect it, as well as their consequences on the breastfeeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0
53

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(129 citation statements)
references
References 12 publications
(17 reference statements)
1
75
0
53
Order By: Relevance
“…Their breasts presented characteristics and functions that limited breastfeeding such as a reduced amount of ducts, even though the residual mammary glands are active and functioning. Lactation occurs at cellular, molecular and behavioral levels, including the anatomy of the woman's breasts, breast milk production and the anatomy and physiology of the stomatognathic system in newborns (9) . Thus, the lactation process is essential for breastfeeding, ensuring the means for women to provide human milk to the child, regardless of whether she is in the immediate or late postpartum period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their breasts presented characteristics and functions that limited breastfeeding such as a reduced amount of ducts, even though the residual mammary glands are active and functioning. Lactation occurs at cellular, molecular and behavioral levels, including the anatomy of the woman's breasts, breast milk production and the anatomy and physiology of the stomatognathic system in newborns (9) . Thus, the lactation process is essential for breastfeeding, ensuring the means for women to provide human milk to the child, regardless of whether she is in the immediate or late postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…In the relational assertions of the Interactive Theory of Breastfeeding, its relational proposition fulfills its descriptive and explanatory role, considering that the biological conditions of the woman interfere in the mother-child interaction dynamic, the mother's role and the woman's decision-making (9) . This seems to explain the findings of this study, which found that the biological conditions preceded successful and unsuccessful outcomes regarding exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations